Advance Identification of Patients With Chronic Conditions and Acute Respiratory Failure at Greatest Risk for High-Intensity, Costly Care - Khandelwal, Nita; May, Peter; Downey, Lois M.; Engelberg, Ruth A.; Curtis, J. Randall (Journal of pain and symptom management, 2022)
Patients with underlying chronic illness requiring mechanical ventilation for acute respiratory failure are at risk for poor outcomes and high costs. Identify characteristics at time of intensive care unit (ICU) admission that identify patients at highest risk for high-intensity, costly care. Retrospective cohort study using electronic health and financial records (2011-2017) for patients requiring ≥48 hours of mechanical ventilation with ≥1 underlying chronic condition at an academic healthcare system. Main outcome was total cost of index hospitalization. Exposures of interest included number and type of chronic conditions. We used finite mixture models to identify the highest-cost group. 4,892 patients met study criteria. Median cost for index hospitalization was $135,238 (range, $9,748 –$3,176,065). Finite mixture modelling identified three classes with mean costs of $89,980, $150,603, and $277,712. Patients more likely to be in the high-cost class were: 1) < 72 years old (OR: 2.03; 95% CI:1.63, 2.52); 2) with dementia (OR: 1.55; 95% CI:1.17, 2.06) or chronic renal failure (OR: 1.27; 95% CI:1.08, 1.48); 3) weight loss ≥ 5% in year prior to hospital admission (OR: 1.25; 95% CI:1.05, 1.48); and 4) hospitalized during prior year (OR: 1.92; 95% CI:1.58, 2.35). Among patients with underlying chronic illness and acute respiratory failure, we identified characteristics associated with the highest costs of care. Identifying these patients may be of interest to healthcare systems and hospitals and serve as one indication to invest resources in palliative and supportive care programs that ensure this care is consistent with patients’ goals.